Development and characteristics of novel polyglycolic acid (PGA) monofilaments for acupoint catgut-embedding therapy applications. Issue 5 (March 2019) - Fu, Shaoju; Lu, Yao; Zhang, Peihua
Acupoint catgut-embedding therapy (ACET) is considered one of the most promising technologies to replace traditional acupuncture therapy in clinical settings. Polyglycolic acid (PGA) monofilament shows great potential for ACET applications due to its advantages of good formability and biodegradability. The ideal embedding materials are required to have excellent swelling, mechanical, and antibacterial properties. For this paper we prepared two types of PGA monofilaments by first using the melt-spinning method and then applying chitosan onto the PGA monofilaments at three different concentrations. The effects of chitosan coating on the characteristics such as surface morphology, swelling, mechanical, FT-IR, antibacterial, and degradable properties of monofilaments were explored. The results show that chitosan layers and fragments were distributed uniformly on the surface of PGA monofilaments. The expansion rate of samples increased with the concentration of the chitosan coat, and samples 1-PGA 3% (98.32 ± 4.24%) and 2-PGA 3% (123.05 ± 2.87%) exhibited the best swelling behavior. Mechanical properties of PGA monofilaments were greatly improved after chitosan coating. There were few interactions between PGA monofilaments and chitosan molecules according to the FT-IR analysis. Antibacterial efficacy and cytocompatibility of PGA monofilaments were greatly enhanced by the chitosan coating treatment. The degradation time was delayed due to the protective function of the chitosan layers, producing a more lasting effect in the treatment process. In conclusion, the novel PGA embedding monofilaments were successfully developed and a chitosan coating concentration of 3% was chosen as the optimum parameter.